Perceived Morality and Antiatheist Prejudice: A Replication and Extension. Issue 3 (3rd July 2019) - Simpson, Ain; McCurrie, Caitlin; Rios, Kimberly
ABSTRACT: Recent evidence suggests that, although moral distrust drives antiatheist prejudice, certain types of morality are central: Perceived atheist moral capacity for caring and compassion appears to be central, whereas perceived atheist moral capacity for fairness, in-group loyalty, deferential respect, or purity/decency is not (Simpson & Rios, 2017). Here, we extend this research. First, we conceptually replicated experimental effects: Manipulating the perception that atheists strongly versus weakly value morality affects antiatheist prejudice much more strongly if the type of morality relates to caring/compassion rather than purity/sanctity ( N = 162; U.S. Christian theists recruited via Amazon Mechanical Turk). This finding was particularly strong among White participants. Second, we provide evidence for cross-national replication of correlational findings among Australian undergraduate theists ( N = 85; recruited from the University of Melbourne) as well as evidence to suggest that the type of perceived morality that predicts prejudice differs according to the social group in question. Specifically, only perceived atheist concern for caring/compassion reliably predicted antiatheist prejudice, whereas perceived Jewish concern caring/compassion and in-group loyalty predicted anti-Jewish prejudice. Results reinforce existing evidence that increasing perceptions of atheist benevolence will help reduce antiatheist prejudice and provide novel support for social-functionalist theories of prejudice.